Piperacillin/tazobactam‐induced immune‐mediated thrombocytopenia in the intensive care unit. (27th September 2016) - Boyce, K.; Brar, H.; Stabler, S. N.
Summary: What is known and objective: Drug‐induced immune‐mediated thrombocytopenia is a rare adverse event that remains a diagnostic challenge, especially in the critically ill population. There are only two previously reported cases of rapid and profound thrombocytopenia after administration of piperacillin/tazobactam. Case summary: A 64‐year‐old man experienced several episodes of isolated thrombocytopenia after receiving piperacillin/tazobactam. Interestingly, the degree of thrombocytopenia varied with the amount of corticosteroid therapy the patient was receiving. Due to the complexity of thrombocytopenia in critically ill patients, other potential causes were extensively worked up and ruled out. What is new and conclusion: We describe the first case of piperacillin/tazobactam‐induced immune‐mediated thrombocytopenia that was mitigated by the administration of corticosteroid therapy. This case highlights the importance of identifying potential drug‐related causes of isolated thrombocytopenia. Abstract : Drug‐induced immune‐modulated thrombocytopenia (DITP) is thought to occur when drug‐dependent antibodies bind to the platelet membrane glycoproteins, leading to signalling for platelet consumption. This graph shows the change in this patient's platelet count after administration and discontinuation of piperacillin/tazobactam.